Novel Three-Day, Community-Based, Nonpharmacological Group Intervention for Chronic Musculoskeletal Pain (COPERS): A Randomised Clinical Trial. - Stephanie J C Taylor; Dawn Carnes; Kate Homer; Brennan C Kahan; Natalia Hounsome; Sandra Eldridge; Anne Spencer; Tamar Pincus; Anisur Rahman; Martin Underwood (PLoS Medicine)
Background Chronic musculoskeletal pain is the leading cause of disability worldwide. The effectiveness of pharmacological treatments for chronic pain is often limited, and there is growing concern about the adverse effects of these treatments, including opioid dependence. Nonpharmacological approaches to chronic pain may be an attractive alternative or adjunctive treatment. We describe the effectiveness of a novel, theoretically based group pain management support intervention for chronic musculoskeletal pain. Methods and findings We conducted a multi-centre, pragmatic, randomised, controlled effectiveness and cost-effectiveness (cost-utility) trial across 27 general practices and community musculoskeletal services in the UK. We recruited 703 adults with musculoskeletal pain of at least 3 mo duration between August 1, 2011, and July 31, 2012, and randomised participants 1.33:1 to intervention (403) or control (300). Intervention participants were offered a participative group intervention (COPERS) delivered over three alternate days with a follow-up session at 2 wk. The intervention introduced cognitive behavioural approaches and was designed to promote self-efficacy to manage chronic pain. Controls received usual care and a relaxation CD. The primary outcome was pain-related disability at 12 mo (Chronic Pain Grade [CPG] disability subscale); secondary outcomes included the CPG disability subscale at 6 mo and the following measured at 6 and 12 mo: anxiety and depression (Hospital Anxiety and Depression Scale [HADS]), pain acceptance (Chronic Pain Acceptance Questionnaire), social integration (Health Education Impact Questionnaire social integration and support subscale), pain-related self-efficacy (Pain Self-Efficacy Questionnaire), pain intensity (CPG pain intensity subscale), the census global health question (2011 census for England and Wales), health utility (EQ-5D-3L), and health care resource use. Analyses followed the intention-to-treat principle, accounted for clustering by course in the intervention arm, and used multiple imputation for missing or incomplete primary outcome data. The mean age of participants was 59.9 y, with 81% white, 67% female, 23% employed, 85% with pain for at least 3 y, and 23% on strong opioids. Symptoms of depression and anxiety were common (baseline mean HADS scores 7.4 [standard deviation 4.1] and 9.2 [4.6], respectively). Overall, 282 (70%) intervention participants met the predefined intervention adherence criterion. Primary outcome data were obtained from 88% of participants. There was no significant difference between groups in pain-related disability at 6 or 12 mo (12 mo: difference -1.0, intervention versus control, 95% CI -4.9 to 3.0), pain intensity, or the census global health question. Anxiety, depression, pain-related self-efficacy, pain acceptance, and social integration were better in the intervention group at 6 mo; at 12 mo, these differences remained statistically significant only for depression (-0.7, 95% CI -1.2 to -0.2) and social integration (0.8, 95% CI 0.4 to 1.2). Intervention participants received more analgesics than the controls across the 12 mo. The total cost of the course per person was £145 (US$214). The cost-utility analysis showed there to be a small benefit in terms of quality-adjusted life years (QALYs) (0.0325, 95% CI -0.0074 to 0.0724), and on the cost side the intervention was a little more expensive than usual care (i.e., £188 [US$277], 95% CI -£125 [-US$184] to £501 [US$738]), resulting in an incremental cost-effectiveness ratio of £5,786 (US$8,521) per QALY. Limitations include the fact that the intervention was relatively brief and did not include any physical activity components. Conclusions While the COPERS intervention was brief, safe, and inexpensive, with a low attrition rate, it was not effective for reducing pain-related disability over 12 mo (primary outcome). For secondary outcomes, we found sustained benefits on depression and social integration at 6 and 12 mo, but there was no effect on anxiety, pain-related self-efficacy, pain acceptance, pain intensity, or the census global health question at 12 mo. There was some evidence that the intervention may be cost-effective based on a modest difference in QALYs between groups. Trial registration ISRCTN Registry 24426731.